Acoustic Measures of Brazilian Transgender Women's Voices: A Case–Control Study - Villas-Bôas, Anna Paula; Schwarz, Karine; Fontanari, Anna Martha Vaitses; Costa, Angelo Brandelli; Cardoso da Silva, Dhiordan; Schneider, Maiko Abel; Cielo, Carla Aparecida; Spritzer, Poli Mara; Rodrigues Lobato, Maria Inês (Frontiers in Psychology, 2021)
The aim of this study was compare acoustic vocal analysis results of a group of transgender women relative to those of cisgender women. Thirty transgender women between the ages of 19 and 52 years old participated in the study. The control group was composed of 31 cisgender women between the ages of 20 and 48 years old. A standardized questionnaire was administered to collect general patient data to better characterize the participants. The vowel /a/ sounds of all participants were collected and analyzed by the Multi-Dimensional Voice Program advanced system. Statistically significant differences between cisgender and transgender women were found on 14 measures: fundamental frequency, maximum fundamental frequency, minimum fundamental frequency, standard deviation of fundamental frequency, absolute jitter, percentage or relative jitter, fundamental frequency relative average perturbation, fundamental frequency perturbation quotient, smoothed fundamental frequency perturbation quotient, fundamental frequency variation, absolute shimmer, relative shimmer, voice turbulence index (lower values in the cases) and soft phonation index (higher values in the cases). The mean fundamental frequency value was 159.046 Hz for the cases and 192.435 Hz for the controls. Through glottal adaptations, the group of transgender women managed to feminize their voices, presenting voices that were less aperiodic and softer than those of cisgender women.